2009
DOI: 10.2337/db09-0278
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide 1/Glucagon Receptor Dual Agonism Reverses Obesity in Mice

Abstract: OBJECTIVEOxyntomodulin (OXM) is a glucagon-like peptide 1 (GLP-1) receptor (GLP1R)/glucagon receptor (GCGR) dual agonist peptide that reduces body weight in obese subjects through increased energy expenditure and decreased energy intake. The metabolic effects of OXM have been attributed primarily to GLP1R agonism. We examined whether a long acting GLP1R/GCGR dual agonist peptide exerts metabolic effects in diet-induced obese mice that are distinct from those obtained with a GLP1R-selective agonist.RESEARCH DES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
317
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(346 citation statements)
references
References 50 publications
21
317
0
Order By: Relevance
“…Nevertheless, an oxyntomodulin analog with an increased affinity for the glucagon receptor in mice, demonstrated increased potency regarding inhibition of food intake and body weight reduction compared to the native oxyntomodulin [65]. This suggests that this potentiated effect was mediated via the glucagon receptor.…”
Section: Oxyntomodulinmentioning
confidence: 93%
“…Nevertheless, an oxyntomodulin analog with an increased affinity for the glucagon receptor in mice, demonstrated increased potency regarding inhibition of food intake and body weight reduction compared to the native oxyntomodulin [65]. This suggests that this potentiated effect was mediated via the glucagon receptor.…”
Section: Oxyntomodulinmentioning
confidence: 93%
“…Further studies have investigated the effects of GLP-1R agonism combined with either glucagon receptor agonism (Pan et al 2006, Day et al 2009 or antagonism (Pocai et al 2009). Although contradictory in nature, these contrasting regimens utilize both the beneficial glucose-lowering effects of GLP-1, combined with either inhibition of glucagon-mediated gluconeogenesis and glycogenolysis (Sinclair & Drucker 2005), and activation of glucagon pathways involved in energy turnover and weight loss (Pocai et al 2009).…”
Section: Cocktail Therapymentioning
confidence: 99%
“…The antagonism of glucagon action on the liver also partly mediates the glucose-lowering effect of biguanides (196) . It has been recently demonstrated that the design of peptides with dual agonism for both the glucagon and the GLP-1 receptors is useful to fight against obesity in mice without any apparent adverse effects (197,198) . This is mainly the result of the antihyperglycaemic, lipolytic, satiating and energy expenditure actions of this combined treatment.…”
Section: Therapeutic Potential Of Modulating Glucagon Secretion and Amentioning
confidence: 99%